Respuesta agronómica del chile jalapeño (capsicum annum) con diferentes dosis de fertilizantes químicos, orgánicos y biológicos. - Briones Tapia, Jefferson Stalin (2023)
The present investigation was carried out in the 2 Chipe Hamburgo sector, belonging to El Triunfo parish, La Maná canton, with the objective of evaluating the agronomic response of jalapeño pepper cultivation (Capsicum annum L.) with different doses of chemical, organic and biological fertilizers. A Randomized Complete Blocks Experimental Design was established, in a 3x2+1 factorial arrangement. The following variables were evaluated: plant height, stem diameter, number of branches, days to flowering, number of fruits, length and diameter of fruits, fruit weight, agronomic yield and an economic analysis by treatments. The results obtained in the vegetative development were: higher plant height in humus leachate (10 ml/l water) with 33.48, 41.80 and 60.55 cm at 30, 45 and 60 days; the stem diameter did not present statistical differences, with NPK (10 ml/l water) reaching 1.28 cm; the variable number of branches presented significant data with humus leachate (10 ml/l water), 14.45 productive branches, regarding the days to flowering; the data with the shortest time until the emission of true flowers occurred in humus leachate ( 10 ml/l water) with 22.50 days from the transplant. In the production variables, a greater number of fruits was recorded with humus leaching (10 ml/l water) with 14.85 fruits, while in the length and diameter of fruits the best results were obtained with humus leaching (10 ml/l water) with 8.31 cm and 4.01 cm respectively. Regarding the weight of fruits, the most prominent treatment was leached humus (10 ml/l water) with an average of 267.30 grams, giving the best yield to leached humus (10 ml/l water) with 48.11 t/ha. In the economic aspect, a better economic benefit ratio was achieved with humus leaching (10 ml/l water), with a return of USD. 0.70 for each monetary unit invested.